Development and evaluation of a buoyancy-driven airflow window with multioperation modes - Eftekhar, Fatemeh; Yoon, Nari; Heo, Yeonsook (Energy and Buildings, 2024)
This study introduces a novel, cost-effective window-integrated passive system (WIPS) that enhances indoor air quality and maintains comfortable temperatures throughout both summer and winter. The WIPS utilizes buoyancy-driven air flow through dual air cavities that alternately preheat or cool the incoming air depending on the season. The system's design was optimized for Seoul, Korea, through computational fluid dynamics (CFD) simulations using Fluent 2021 R2 software, which employed a Reynolds-Averaged Navier-Stokes (RANS) model with RNG κ-ε turbulence modeling. Key design adjustments included the use of glass and unplasticized polyvinyl chloride (UPVC) to minimize unintended airflow, as well as modifications to the geometry and size of the air cavities to maximize efficient air flow and thermal effectiveness. The optimized design demonstrated significant improvements in thermal performance, achieving a preheating effect up to 35 °C in winter and reducing indoor temperatures by 10 °C in summer. These results underline the potential of WIPS to provide a sustainable solution for building ventilation and climate control.
Keywords: Airflow window system; Buoyancy-driven; Buoyancy-driven ventilation; Computational fluid; Computational fluid dynamic; Fluid-dynamics; Integrated passives; Passive cooling; Passive systems; Window system; Airflow window system; Buoyancy-driven ventilation; Computational fluid dynamics (CFD); Passive cooling; Preheating